1986
DOI: 10.1029/jd091id07p07765
|View full text |Cite
|
Sign up to set email alerts
|

Meridional eddy diffusion model of the transport of atmospheric carbon dioxide: 1. Seasonal carbon cycle over the tropical Pacific Ocean

Abstract: An extensive set of atmospheric CO2 observations were obtained during the First Global Geophysical Experiment (FGGE) Hawaii to Tahiti Shuttle expedition of 1979–1980. These data have been examined using a one-dimensional meridional diffusive transport model of the atmospheric circulation. The observed CO2 concentration field was first decomposed into three parts: a seasonal component consisting of two harmonic functions of time, with periods of 1 year and 6 months; a mean annual north-south concentration profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…With a geochemical model portraying sources and sinks of CO 2 with northsouth resolution (23,40), we refined the regional representation of the carbon cycle that I had worked on earlier with Bert Bolin in Sweden (8). Still more important as groundwork for a later study, we worked to identify all of the most important components of the global carbon cycle, and to characterize them using up-to-date geochemical data.…”
Section: Negotiating With Three Agenciesmentioning
confidence: 98%
“…With a geochemical model portraying sources and sinks of CO 2 with northsouth resolution (23,40), we refined the regional representation of the carbon cycle that I had worked on earlier with Bert Bolin in Sweden (8). Still more important as groundwork for a later study, we worked to identify all of the most important components of the global carbon cycle, and to characterize them using up-to-date geochemical data.…”
Section: Negotiating With Three Agenciesmentioning
confidence: 98%
“…Many studies have interpreted the observed meridional gradients of tracers such as CO 2 , chlorofluorocarbons (CFCs), and SF 6 in terms of a single interhemispheric exchange time (e.g., Heimann and Keeling 1986;Maiss and Levin 1994;Bowman and Cohen 1997). The underlying conceptual model for these exchange times, typically found to be on the order of 1 yr, is a simple two-box model with each box being a hemisphere (e.g., Bowman and Cohen 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The slow exchange between the three main zones gives the appearance of semi‐permeable “barriers” to transport in the subtropics. As a result of the slow exchange between the main zones, the time required to mix air from the extratropics of the one hemisphere to the extratropics of the other hemisphere, passing through the tropics, is on the order of 1.8 years [ Heimann and Keeling , 1986; Prather et al , 1987; Cunnold et al , 1994; Bowman and Cohen , 1997; Bowman and Erukhimova , 2004].…”
Section: Introductionmentioning
confidence: 99%